Second Trimester Umbilical Cord Coiling Index and Perinatal Outcomes - Yusuf Aytaç Tohma; Mehmet Metin Altay; Derya Turgut; Selcan Coşkun; Eylem Ünlübilgin; Sertaç Esin; Orhan Gelişen; Okyar Erol (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Umbilical cord usually seems simple functionally and structurally but it's the life link between fetus and mother that was critically important for growing fetus. The aim of this study is to evaluate the effect of early umbilical cord coiling index on perinatal outcomes. STUDY DESIGN: 221 patients with singleton, alive pregnancies between 18-24 gestational weeks were included in our study and have been evaluated prospectively. Patients’ age, obstetric history, BMI before pregnancy, history of smoking was registered. Umbilical arter coiling index was also calculated. Perinatal problems such as preeclampsia, gestational diabetes mellitus (GDM), intrauterine growth restriction (IUGR), small for gestational age (SGA) and birth weight, gestational age at birth, and newborn intensive care unit need were recorded. RESULTS: There was a negative correlation between antenatal umbilical cord coiling index (aUCI) and gestational age. The birth weights were lower in patients with hypocoiled umbilical cord structure. Preeclampsia was seen in 3.93% of patients with normal aUCI, 26.09 % in hypocoiling group, and 21.05 % in hypercoiling group. The percentage of patients with normal aUCI who had GDM is 2.18, 13.04% of patients with hypercoiling and 10.53% of patients with hypocoiling had GDM. The percentage of patients with normal aUCI who had IUGR is 3.49, 21.74% of patients with hypercoiling and 5.26% of patients with hypocoiling had IUGR. According to aUCI there was a statistical difference in GDM, preeclampsia and IUGR and different from the literature, in our study, we found a statistically significant difference in hypercoiled umbilical cords in terms of preeclampsia. Newborns with hypercoiling or hypocoiling were needed more neonatal intensive care unit. CONCLUSIONS: There was measured correlation between umbilical cord diameter and aUCI between 18-24 weeks and perinatal outcome but new prospective studies about umbilical artery morphology and perinatal outcomes are also needed.